Program Pembinaan Calon Peserta Kompetisi Sains Madrasah (KSM) Nasional di MTs Guppi Majene - Hikmah Hikmah; Fardinah Fardinah; Apriyanto Apriyanto; Nurfadila Nurfadila (To Maega : Jurnal Pengabdian Masyarakat, 2024)
The problem of MTs Guppi Majene partners is the limited human resources that can guide the preparation of the Madrasah Science Competition (KSM) to the National level, and students still need to become familiar with the curriculum being contested. Moreover, the forms of KSM questions differ greatly from the general material in schools. This activity aims to improve students' ability to solve mathematical problems, especially solving KSM problems. This community service program is carried out by observation, implementation, and evaluation methods, with four stages, namely the beginning, preparation, implementation, and final stages. Based on hypothesis testing, a p-value of 0.008 was obtained, which means an increase in students' ability to solve KSM questions. The result of the activity was the selection of 2 students representing MTs Guppi to participate in the 2023 district-level KSM.